Survival Rate and Food Utilization Rate of the Red Nila Fish (Oreochromis sp) Utilizing synthetic feed additives Seaweed (Gracilaria sp) - Rovina Andriani; Fatma Muchdar; Syahnul Sardi Titaheluw (Journal of Global Sustainable Agriculture, 2022)
In the fish farming business, feed is the highest operational cost, which reaches more than 60% of the total production cost. Therefore, the fish feed can be processed independently to reduce production costs in aquaculture businesses. This study aimed to determine the survival rate and feed efficiency of red tilapia (Oreochromis sp) fed artificial feed with the addition of seaweed (Gracilaria sp). This research was carried out from June to September 2021 at the Integrated Laboratory of Khairun University. This study used four treatments, and each treatment was repeated three times. The treatment tried is A (Artificial feed with the addition of Gracilaria sp 10 gr); B (Artificial feed with the addition of Gracilaria sp 20 gr; C (Artificial feed with the addition of Gracilaria sp 30 gr); and D (Artificial feed without the addition of Gracilaria sp.). The research variables included calculating the survival rate (SR), Feed Conversion Ratio (FCR), and observing water quality during the study. The highest survival value was in treatment B at 97.78%, while the lowest was in treatment A at 73.33%. The highest feed conversion ratio was in treatment D, 1.97, followed by treatments A and B, 1.48, and the lowest in treatment C, 0.64. The results of water quality measurements during the study, namely DO, range from 6-6.8 in all treatments, pH ranged from 7-7.6, and temperature ranged from 28-290C. The best survival rate (SR) of red tilapia-fed artificial feed with the addition of Gracilaria sp seaweed was best in treatment B, 97.78%, and the best feed conversion ratio (FCR) was in treatment C, which was 0.64 g.